Can a native rodent species limit the invasive potential of a non-native rodent species in tropical agroforest habitats? - Stuart, Alexander M.; Prescott, Colin V.; Singleton, Grant R. (Wiley, 2016)
Little is known about native and non‐native rodent species interactions in complex tropical agroecosystems. We hypothesised that the native non‐pest rodentRattus everettimay be competitively dominant over the invasive pest rodentRattus tanezumiwithin agroforests. We tested this experimentally by using pulse removal for three consecutive months to reduce populations ofR. everettiin agroforest habitat, and assessed over 6 months the response ofR. tanezumiand other rodent species.RESULTSFollowing removal,R. everettiindividuals rapidly immigrated into removal sites. At the end of the study period,R. tanezumiwere larger and there was a significant shift in their microhabitat use with respect to the use of ground vegetation cover following the perturbation ofR. everetti. Irrespective of treatment,R. tanezumiselected microhabitat with less tree canopy cover, indicative of severely disturbed habitat, whereasR. everettiselected microhabitat with a dense canopy.CONCLUSIONOur results suggest that sustained habitat disturbance in agroforests favoursR. tanezumi, while the regeneration of agroforests towards a more natural state would favour native species and may reduce pest pressure in adjacent crops. In addition, the rapid recolonisation ofR. everettisuggests this species would be able to recover from non‐target impacts of short‐term rodent pest control. © 2015 Society of Chemical Industry